2017
DOI: 10.1111/iej.12845
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary assessment of a new dedicated endodontic software for use with CBCT images to evaluate the canal complexity of mandibular molars

Abstract: 3D Endo software features the automatic detection and measurement of several anatomical canal parameters, and is a promising tool for the study of canal complexity in vivo. The unpredictable anatomy of the mesial roots of mandibular molars highlights the value of a three-dimensional preoperative evaluation of each case. The proposed scoring system aims to provide the clinician with an overall assessment of canal complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
1
28
0
5
Order By: Relevance
“…This result is in agreement with those from previous studies demonstrating that, regardless of the features of the NiTi instruments, the resistance to cyclic fatigue can be increased by operating the instrument in a reciprocating motion, rather than CR (8,19,26,27,16,34). These results suggest that this motion could increase the safety when preparing difficult cases (severe curvatures, S-shaped canals), where the risk of intra-canal failure is higher (31,36). OGP 90°presented the highest mean time-to-fracture, and the Weibull analysis confirmed the longest survival with a very high predictability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in agreement with those from previous studies demonstrating that, regardless of the features of the NiTi instruments, the resistance to cyclic fatigue can be increased by operating the instrument in a reciprocating motion, rather than CR (8,19,26,27,16,34). These results suggest that this motion could increase the safety when preparing difficult cases (severe curvatures, S-shaped canals), where the risk of intra-canal failure is higher (31,36). OGP 90°presented the highest mean time-to-fracture, and the Weibull analysis confirmed the longest survival with a very high predictability.…”
Section: Discussionsupporting
confidence: 91%
“…Instead of directly simulating clinical conditions, cyclic fatigue tests aim to control variables (e.g., curvature angle, position and axial motion) to obtain a fair mechanical comparison between instruments or motions (7,10,11,(29)(30)(31). However, abrupt curvatures in the buccal-lingual plane might not be detectable in traditional periapical radiographs, especially when the canals are confluent (31,36). However, abrupt curvatures in the buccal-lingual plane might not be detectable in traditional periapical radiographs, especially when the canals are confluent (31,36).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, CBCT has been used in conjunction with specialized software (3DEndo ® , Dentsply Sirona, Ballaigues, Switzerland) to evaluate the complexity of root canals (Gambarini et al . ) prior to treatment. Patel et al .…”
Section: Assessment Of Root Canal Anatomymentioning
confidence: 99%
“…Cone beam computed tomography examination improves the identification, location and appreciation of teeth with anomalous anatomy, for example dens invaginatus (Patel 2010. More recently, CBCT has been used in conjunction with specialized software (3DEndo â , Dentsply Sirona, Ballaigues, Switzerland) to evaluate the complexity of root canals (Gambarini et al 2018) prior to treatment. Patel et al (2019) found 3DEndo â , software, followed by CBCT, was found to be more desirable for the evaluation of root canal anatomy, working lengths and also reducing the clinician's stress levels than PR.…”
Section: Assessment Of Root Canal Anatomymentioning
confidence: 99%
“…The choice of such canals was made to remove the bias associated with the clinical variability of endodontic anatomy (Gambarini et al . ). Moreover, canal curvatures may lead to bending stress, so the present study was designed to limit variables by focusing only on analysing the results of the clinical torsional stress derived from the two different modus operandi .…”
Section: Discussionmentioning
confidence: 97%